Dana gas sukuk default: a juristic analysis of court judgement - Abdullahi Busari, Saheed; Abdul Aziz, Akhtarzaite; Zakariyah, Luqman; Amanullah, Muhammad Amanullah (Emerald Publishing Limited, 2019)
Purpose – This study aims to analyse the facts of the case in the judgement made by the High Court of Justice, England, UK, in the case of Dana Gas Public Joint Stock Company (PJSC) v. Dana Gas Sukuk Limited (Ltd.) and Ors. Design/methodology/approach – This study uses descriptive and juristic analysis to explain the factual terms in the case of Dana Gas sukuk default. It also uses juristic opinions to analyse the underpinning argument in the Dana Gas court case between the decision of Sharjah Court, UAE, and the English Court, UK. Findings – The study concluded that despite the position of Dana Gas PJSC that specific element of the mu darabah sukuk is non-Sharī’ah-compliant, the English court decision which established the enforceability of the purchase undertaking seems to be fair based on the Islamic maxims such as “Difficult situation cannot violate the right of other” and “The conditional matters among Muslims are binding.” Research limitations/implications – The impact of this study is that Dana Gas sukuk default has thought stakeholders of Sukuk investment lessons on the importance of documentation and consideration of tighter clauses to ensure its bindingness in the law court. Hence, this study is expected to be a contribution towards the call for standardization of the role of Sharī’ah scholars across the globe. Originality/value – This study illustrates the fact in the case of Dana Gas sukuk default and analyses the court’s decision from a fiqh perspective.